Towards extra-jurisdictional environmental management in combating transnational environmental crimes in Malaysia from a legal aspect - Kamaruddin, Hanim; Azham Marwan, Muhamad (International Journal of Engineering and Technology, 2018)
Environmental deterioration in Southeast Asia region can be attributed to illegal logging and timber smuggling which contributes to deforestation, wildlife smuggling, black-market transactions in ozone-depleting substances and dumping of other forms of hazardous wastes and chemical, illegal open burning incidents that can lead to air pollution contributing to transnational impacts. Controlling activities that are taking place within one State resulting to environmental impacts in another State is not uncommon in environmental issues and thus, such activities are construed as environmental crimes at times. Hence, any illegal activities within another jurisdiction must be addressed efficiently as the conduct of such activities are becoming increasingly sophisticated and complex partly due to the nature of transnational activities that operate beyond national boundaries. This article will discuss transnational environmental crime in Malaysia and Southeast Asia region and assess the application of adopting extra-jurisdictional approach to combat transnational environmental crime by drawing the example from Singapore’s experience of passing the Transboundary Haze Pollution Act 2014 to tackle challenges of haze pollution that are caused by activities in another State. The finding of this article suggests that extra-jurisdictional legislation is a common management tool in international law based on the international principle of territorial sovereign applies to conduct of a State within its territory. There seemed to be an exception that stems from a principle known as ‘objective territoriality principle’ under international law that allows another State to make claims against another State that commits environmental crime resulting to transnational impacts. The efficiency of extra-jurisdictional approach will be analysed based on Malaysia’s experiences in tackling transnational environmental crimes by reviewing domestic policies, local legislations and relevant international agreements to ensure that environmental protection is sustained.
Keywords: Environment; Transnational; Crime; Malaysia; Extra-jurisdictional